Crime of Collective Violence in Ambon City: Criminological Study of Locus Delicti, Time Patterns and Social Motives - Syah Awaluddin Uar; Ahmad Lonthor; Soeleman Djaiz Baranyanan; Ridwan F. Lestaluhu; Siti Zainab Yanlua (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Collective violence remains a significant social issue in Ambon City, particularly over the past two years. The increasing intensity and spread of group violence incidents underscore the importance of spatial, temporal, and social analysis in understanding the emerging patterns. This study aims to identify the distribution patterns of locus delicti, temporal trends, and the underlying social motives behind collective violence in Ambon during 2023–2024. This research employed a descriptive qualitative method with data collected through field observations, informal interviews with community members and security personnel, as well as documentation from police reports and local media. The results indicate that collective violence incidents were concentrated in densely populated urban areas, public facilities, and nightlife zones. By 2024, the locus of violence began shifting to suburban and symbolic locations such as Merdeka Square. Temporally, most incidents occurred at night until early morning, coinciding with weakened social control. Contributing criminogenic factors include weak community social control, subcultural violence within village-based youth groups, neglected environments, and the contagion effect of crowds in public spaces. This study concludes that collective violence in Ambon City is driven not only by situational and individual factors but also by environmental conditions, crime opportunities, and collective norms that legitimize violent behavior. This study recommends intensifying nighttime patrols, initiating inter-community youth dialogues, and fostering community-based early warning systems to prevent the escalation of group violence in the future.